Association of Diabetic Autonomic Neuropathy with Red Blood Cell Aldose Reductase Activity - Gupta, Pawan; Verma, Narsingh; Bhattacharya, Sandeep; Mahdi, Abbas A.; Usman, Kauser; Tiwari, Sunita; Bhardwaj, Kshitij (Canadian journal of diabetes, 2014)
Activation of polyol pathway based on increased activity of aldose reductase (AR) has been implicated in the development of diabetic complications including diabetic autonomic neuropathy (DAN). The relationship between DAN and hyperglycemia-induced activation of polyol pathway is still uncertain. In the present study, we investigate the association between aldose reductase activity and diabetic autonomic neuropathy by measuring AR level in red blood cells (RBC). In this study, 145 subjects with diabetes with or without DAN and 32 subjects without diabetes have been included. All subjects have been investigated for autonomic function tests and RBC aldose reductase activity. DAN was defined if results of any 2 of the tests of parasympathetic function were abnormal. RBC aldose reductase level was determined spectrophotometrically and expressed as unit/g of hemoglobin. The values were expressed as mean ± standard deviation, and ANOVA test has been applied for comparison between groups. RBC aldose reductase activity was found to be significantly higher in people with diabetes with autonomic neuropathy in comparison to people with diabetes without autonomic neuropathy and healthy individuals without diabetes. Aldose reductase (AR) level ranges from 0.8 units/g Hb to 14.2 units/g Hb. The mean AR level was 8.6±2.95 units in subjects of DM with autonomic neuropathy, while mean AR level was 4.1±1.78 units and 2.0±0.89 units in people with diabetes without neuropathy and normal healthy individuals, respectively (p<0.001). High aldose reductase activity is associated with the presence of autonomic neuropathy in subjects of type 2 DM. L’activation de la voie des polyols du fait de l’augmentation de l’activité de l’aldose réductase (AR) a été impliquée dans le développement des complications liées au diabète, y compris la neuropathie diabétique autonome (NDA). Le lien entre la NDA et l’activation de la voie des polyols induite par l’hyperglycémie est encore incertaine. Dans l’étude actuelle, nous examinons le lien entre l’activité de l’aldose réductase et la neuropathie diabétique autonome en mesurant la concentration d’AR dans les globules rouges (GR). Dans cette étude, 145 sujets diabétiques ayant ou non une NDA, et 32 sujets non diabétiques ont été inclus. Tous les sujets ont subi des explorations du fonctionnement du système nerveux autonome et de l’activité de l’aldose réductase dans les GR. La NDA était définie si les résultats de l’une des deux explorations du fonctionnement du système nerveux parasympathique étaient anormaux. La concentration de l’aldose réductase dans les GR était déterminée par spectrophotomètre et exprimée en U/g d’hémoglobine. Les valeurs étaient exprimées par la moyenne ± l’écart type, et l’analyse de la variance a été appliquée pour comparer les groupes. L’activité de l’aldose réductase dans les GR s’était avérée significativement plus élevée chez les diabétiques ayant une neuropathie autonome que chez les diabétiques n’ayant pas de neuropathie autonome et les individus non diabétiques en santé. La concentration de l’aldose réductase (AR) variait de 0,8 U/g d’Hb à 14,2 U/g d’Hb. La concentration moyenne d’AR était de 8,6 ± 2,95 unités chez les sujets ayant un DS et une neuropathie autonome, tandis que la concentration moyenne d’AR était de 4,1 ± 1,78 unités et de 2,0 ± 0,89 unités respectivement (p<0.001) chez les diabétiques n’ayant pas de neuropathie et chez les individus ayant une bonne santé. Une forte activité de l’aldose réductase est associée à la présence d’une neuropathie autonome chez les sujets ayant le DS de type 2.